Canonical Polymorphisms of Ramsey Structures and the Unique Interpolation Property - Bodirsky, Manuel; Bodor, Bertalan (Proceedings of the 36th Annual ACM/IEEE Symposium on Logic in Computer Science, 2021)
Constraint satisfaction problems for first-order reducts of finitely bounded homogeneous structures form a large class of computational problems that might exhibit a complexity dichotomy, P versus NP-complete. A powerful method to obtain polynomial-time tractability results for such CSPs is a certain reduction to polynomial-time tractable finite-domain CSPs de-fined over k-types, for a sufficiently large k. We give sufficient conditions when this method can be applied and illustrate how to use the general results to prove a new complexity dichotomy for first-order expansions of the basic relations of the spatial reasoning formalism RCC5.